Structural Changes of Sodium Warfarin in Tablets Affecting the Dissolution Profiles and Potential Safety of Generic Substitution - Jan Muselík; Martina Urbanova; Eva Bartoníčková; Jakub Palovčík; David Vetchý; Jiří Czernek; Larisa Janisova; Nadiia Velychkivska; Aleš Franc; Jiří Brus (MDPI AG, 2021)
At present, the risk of generic substitutions in warfarin tablets is still being discussed. The aim of this study was to assess whether API interactions with commonly used excipients may affect the safety of generic replacement of warfarin sodium tablets. These interactions were observed during an accelerated stability study, and the effect of the warfarin solid phase (crystalline/amorphous form) as well as the API particle size distribution was studied. Commercial tablets and prepared tablets containing crystalline warfarin or amorphous warfarin were used. In addition, binary mixtures of warfarin with various excipients were prepared. The structural changes before and after the stability study were monitored by dissolution test in different media, solid-state NMR spectroscopy and Raman microscopy. During the stability study, the conversion of the sodium in warfarin to its acid form was demonstrated by some excipients (e.g., calcium phosphate). This change in the solid phase of warfarin leads to significant changes in dissolution, especially with the different particle sizes of the APIs in the tablet. Thus, the choice of suitable excipients and particle sizes are critical factors influencing the safety of generic warfarin sodium tablets.